THE INFLUENCE OF ORGANIZATIONAL DESIGN AND BUREAUCRATIC STRUCTURE ON EMPLOYEE PERFORMANCE IN THE DEVELOPMENT ADMINISTRATION DIVISION OF THE REGIONAL SECRETARIAT OF SOUTH BURU REGENCY - Kristina Latbual; Samson Laurens; Stanislaus Kostka Ohoiwutun (SOSIOEDUKASI, 2026)
This study examines the influence of organizational design and bureaucratic structure on employee performance in the Development Administration Division of the Regional Secretariat of South Buru Regency. The research employs a quantitative approach using multiple linear regression analysis to test the relationship between variables. Data were analyzed through t-tests, F-tests, and the coefficient of determination to measure both partial and simultaneous effects. The findings reveal that organizational design has a positive and significant effect on employee performance, particularly through clear task distribution, appropriate functional alignment, and effective coordination mechanisms. Bureaucratic structure also demonstrates a positive and significant influence, with stronger impact reflected in clear authority lines, consistent implementation of standard operating procedures (SOPs), and effective supervision systems. Simultaneously, both variables significantly affect employee performance, with a coefficient of determination indicating that a substantial proportion of performance variation can be explained by these structural factors. The study concludes that improving employee performance requires integrated reforms in organizational design and bureaucratic strengthening. Strengthening structural governance mechanisms is essential to creating a more effective, professional, and results-oriented development administration capable of supporting sustainable regional development.